A protocol for visualizing active cathepsin K in osteoclasts with a quenched-fluorescence-activity-based probe - Aleksandra Korba; Izabela Ciastoń; Joanna Kozieł; Paulina Kasperkiewicz (STAR Protocols, 2023)
Summary: Herein, we provide a protocol for visualizing active osteoclast cathepsin K (CatK) with the quenched-fluorescent-activity-based probe qTJK17. We describe steps for isolating peripheral blood mononuclear cells, their differentiation into osteoclasts, and TRAP staining using an acid phosphatase leukocyte kit. We then detail visualization of active CatK. The probe qTJK17 includes a reactive group, acyloxymethylketone, that binds to the CatK active site, recognition sequence, and fluorescence donor-acceptor pair. This protocol can determine the exact localization of active CatK in osteoclasts.For complete details on the use and execution of this protocol, please refer to Janiszewski et al. (2023).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.